Group IV Light Sources to Enable the Convergence of Photonics and Electronics - Saito, Shinichi; Gardes, Frederic Yannick; Al-Attili, Abdelrahman Zaher; Tani, Kazuki; Oda, Katsuya; Suwa, Yuji; Ido, Tatemi; Ishikawa, Yasuhiko; Kako, Satoshi; Iwamoto, Satoshi; Arakawa, Yasuhiko (Frontiers in Materials, 2014)
Group IV lasers are expected to revolutionize chip-to-chip optical communications in terms of cost, scalability, yield, and compatibility to the existing infrastructure of silicon industries for mass production. Here, we review the current state-of-the-art developments of silicon and germanium light sources towards monolithic integration. Quantum confinement of electrons and holes in nano-structures has been the primary route for light emission from silicon, and we can use advanced silicon technologies using top-down patterning processes to fabricate these nano-structures, including fin-type vertical multiple quantum wells. Moreover, the electromagnetic environment can also be manipulated in a photonic crystal nano-cavity to enhance the efficiency of light extraction and emission by the Purcell effect. Germanium is also widely investigated as an active material in Group IV photonics, and novel epitaxial growth technologies are being developed to make a high quality germanium layer on a silicon substrate. To develop a practical germanium laser, various technologies are employed for tensile-stress engineering and high electron doping to compensate the indirect valleys in the conduction band. These challenges are aiming to contribute towards the convergence of electronics and photonics on a silicon chip.